Estimating the threshold level of public expenditure and fiscal deficit in the United Arab Emirates (UAE): evidence from Kuznets Curve Hypothesis - Gamal, Awadh Ahmed Mohammed (Tanjung Malim, 2023)
Estimating the threshold level of public expenditure and fiscal deficit in the United Arab Emirates (UAE): evidence from Kuznets Curve Hypothesis by Gamal, Awadh Ahmed Mohammed